Feasibility studies of government subsidized bus rapid transit (brt) in kuala lumpur - Nurul Saadiah Bt. Abdul Manan, Nurul Saadiah (2009)
This paper describes an attempt made to study the feasibility studies on subsidized bus rapid transit (BRT) in Kuala Lumpur. The aim of the study was to propose a new system on more effective public transport, and to encourage the citizen to use public transport.